Pengaruh Financial Literacy, Locus of Control dan Lifestyle Terhadap Financial Management Behavior Pada Mahasiswa Penerima Beasiswa Pengguna Shopee Paylater Di Universitas Trunojoyo Madura - hasyimi, rizqi dian; Dwi Purnomo, Arie Setyo (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to identify the influence of financial literacy, locus of control, and lifestyle on financial management behavior among students of Trunojoyo Madura University who are scholarship recipients and users of Shopee Paylater service. This research employs an associative quantitative method. The data sources utilized include primary data obtained directlyfrom respondents through questionnaire completion, as well as secondary data obtained from the Administrative Office of Trunojoyo Madura University. The number of respondents involved in this study is 100 students. Sampling method employs probability sampling with purposive sampling approach. Multiple linear regression analysis using SPSS version 25 is utilized to test hypotheses. The results of this study indicate that financial literacy and locus of control variables have a positive and significant influence on financial management behavior among scholarship recipients who use Shopee Paylater service. However, the lifestyle variable is found to have no significant impact or it can be said that the lifestyle variable does not affect financial management behavior among scholarship.